A Comparative Study of Israeli and United States of America Teacher Trainers on Sockett's Four Models of Teacher Education - J.E. Hollenbeck; H. Ezer; M. Mevorach (University of Sofia, 2014)
This study examined the beliefs of teacher educators and their impact on pre-service teachers as they entered the profession and identified commonalities between Israel and the United States teacher education programs. 150 teacher educators were surveyed from a cross section of teacher educators on Hugh Sockett's four teaching models proposed for teacher preparation from Israel and the United States. The research queried three questions: (1) teacher educators' evaluation of the field of teacher education, (2) beliefs regarding the four basic components of teacher education as described by Sockett, and (3) beliefs regarding teacher education in the institution they taught.